The digital pill : what everyone should know about the future of our healthcare system - Fleisch, Elgar; Franz, Christoph; Herrmann, Andreas (Emerald Publishing Limited, 2021)
Information technology is changing healthcare in numerous wide-ranging aspects, including significantly improving the overall quality of patient care and therefore helping to reduce limitations in people's daily lives. 'The Digital Pill' reflects on how digital technologies can combat chronic diseases including diabetes, cancer, cardiovascular, respiratory and neurodegenerative diseases as well as mental disorders. Chronic diseases touch every family, generate infinite suffering and cause the lion's share of every countries' healthcare spending across the world. The authors carefully study a broad selection of contemporary companies and healthcare organizations that are shaping digital healthcare. They report pioneering cases from large and small technology, insurance, and pharmaceutical companies as well as healthcare providers of all sorts across the globe and bring forward patterns and corner stones of an affordable and patient centric digital healthcare. 'The Digital Pill' is essential reading for anyone working in, engaged with or interested in understanding the future of healthcare.